STRATEGY OF IMPOLITENESS UTTERED BY MOBILE LEGEND: BANG BANG PLAYERS - Rizky, Nadia; Laila, Malikul (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Social media gaming is a recent trend that allows most teenagers to express themselves freely. As the tendency changes toward public entertainment, in this case esports broadcasting, the bulk of them turn into spectators. However, the manner in which they express themselves is frequently regarded as unethical. This means that their expressions frequently transcend the norm, as evidenced by several unpleasant comments. With this in mind, the aim of this research is to identify the various forms and intentions of impolite language strategies used in live comments on YouTube during broadcasts of the Mobile Legends Premier League (MPL) Indonesia Season 12. Aside from that, the researchers explored how incivility standards were explained in YouTube Mobile Legends: Bang Bang live comments. This study is a descriptive qualitative study. Culpeper's (1996) impoliteness theory is used by researchers. In this study, data was gathered by observation and note-taking. The data for this study came from harsh text comments on a match video on the official Mobile Legends: Bang Bang YouTube channel. According to the findings of the study, four types of rudeness are used: outright bald on record impoliteness, positive impoliteness, negative impoliteness, sarcasm or mock impoliteness. The researchers, however, did not detect withhold politeness type. Aside from that, the researchers found that there is a thing that may be considered breaching the impolite norms, notably spamming behaviors, based on the results of the researched data.